Low-level shRNA cytotoxicity can contribute to MYC-induced hepatocellular carcinoma in adult mice - Beer, Shelly; Bellovin, David I; Lee, Joyce; Komatsubara, Kimberly; Wang, Lora S; Koh, Huishan; Börner, Kathleen; Storm, Theresa A; Davis, Corrine R; Kay, Mark A; Felsher, Dean W; Grimm, Dirk (Molecular therapy, 2010)
Short hairpin RNAs (shRNAs) have emerged as a novel therapeutic modality, but there is increasing concern over nonspecific effects in vivo. Here, we used viral vectors to express shRNAs against endogenous p53 in livers of conditional MYC-transgenic mice. As expected, the shRNAs silenced hepatic p53 and accelerated liver tumorigenesis when MYC was concurrently expressed. Surprisingly, various irrelevant control shRNAs similarly induced a rapid onset of tumorigenesis, comparable to carbon tetrachloride (CCl4), a potent carcinogen. We found that even marginal shRNA doses can already trigger histologically detectable hepatoxicity and increased hepatocyte apoptosis. Moreover, we noted that shRNA expression globally dysregulated hepatic microRNA (miRNA) expression, and that shRNA levels and activity further increased in the presence of MYC. In MYC-expressing transgenic mice, the marginal shRNA-induced liver injury sufficed to further stimulate hepatocellular division that was in turn associated with markedly increased expression of the mitotic cyclin B1. Hence, even at low doses, shRNAs can cause low-level hepatoxicity that can facilitate the ability of the MYC oncogene to induce liver tumorigenesis. Our data warrant caution regarding the possible carcinogenic potential of shRNAs when used as clinical agent, particularly in circumstances where tissues are genetically predisposed to cellular transformation and proliferation.
Published online 20 October 2009
Gesehen am 04.01.2023